The regulation of health care providers' payments when horizontal and vertical differentiation matter (2012)
This paper analyzes the regulation of payment schemes for health care providers competing in both quality and product differentiation of their services. The regulator uses two instruments: a prospective payment per patient and a cost reimbursement rate. When the regulator can only use a prospective payment, the optimal price involves a trade-off between the level of quality provision and the level of horizontal differentiation. If this pure prospective payment leads to underprovision of quality and overdifferentiation, a mixed reimbursement scheme allows the regulator to improve the allocation efficiency. This is true for a relatively low level of patients' transportation costs. We also show that if the regulator cannot commit to the level of the cost reimbursement rate, the resulting allocation can dominate the one with full commitment. This occurs when the transportation cost is low or high enough, and the full commitment solution either implies full or zero cost reimbursement. © 2012 Elsevier B.V.